ChemInform Abstract: Key Study on the Potential of Hydrazine Bisborane for Solid‐ and Liquid‐State Chemical Hydrogen Storage. Issue 28 (July 2015) - Pylypko, Sergii; Petit, Eddy; Yot, Pascal G.; Salles, Fabrice; Cretin, Marc; Miele, Philippe; Demirci, Umit B.
Abstract The title compound, N2H4(BH3)2, is prepared from a mixture of freshly ground [N2H5][HSO4] and NaBH4 in THF (Ar‐filled glovebox, round‐bottom flask, 40 °C, 42—90 h, 87% yield).